MAPPING THE LANDSCAPE OF COLLABORATIVE POLICING: A BIBLIOMETRIC ANALYSIS OF GLOBAL RESEARCH TRENDS - Teuku Fahmi; Iqrak Sulhin; Anggi Aulina Harahap (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
Collaborative policing is a multifaceted approach that involve the collaboration of various police agencies and community groups to improve crime prevention, information sharing, and public safety. This approach has gained prominence because it can address complex social problems and enhance public safety through collective efforts. This study aimed to determine research trends in collaborative policing using bibliometric analysis combining five leading journal databases, including Scopus, ScienceDirect, SageJournals, Emerald Insight, and Taylor & Francis. A total of 58 articles published up to May 2025 were then subjected to a series of identification processes, including the profiles of the most contributing authors, number of citations, publication types, and keyword co-occurrence. VOSviewer was used to analyze and visualize relationships in the academic literature and identify trends, gaps, and contributions from previous research. The results show that collaborative policing research has undergone significant evolution and is concentrated in Western countries, particularly the United States, the United Kingdom, and Australia. Analysis of keyword co-occurrence over time confirms a shift in focus from fundamental concepts, such as community policing to more structured, measurable, and evidence-based approaches such as evidence-based policing and interagency collaboration. This emphasizes the importance of partnerships, information sharing, and multi-agency collaboration as a key focus of current research. This study identifies gaps for further research covering a range of themes, such as quantitative impact evaluation of collaborative programs, challenges in implementation on the ground, the role of technological innovation in facilitating partnerships, and strategies for sustainably enhancing community engagement.